Analisis Keterampilan Gerak Dasar Lokomotor dan Manipulatif melalui Tes TGMD-2 pada Siswa Sekolah Dasar SD Negeri 2 Surondakan - Febrianto, Nendra; Sugeng Sulendro; Khamim Hariyadi (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2026)
This study aims to analyze the basic locomotor and manipulatif motor skills of students at Surondakan 2 Elementary School using the Test of Gross Motor Development-2 (TGMD-2) instrument. The study used a quantitative descriptive method with 28 third-grade students as research subjects. Data collection was carried out through tests and direct observation using the TGMD-2 instrument which includes six locomotor skills and six manipulatif skills. Data were analyzed through raw score calculations, conversion to standard scores, and determination of Gross Motor Quotient (GMQ) values ​​based on TGMD-2 norms. The results showed that students' GMQ scores ranged from 67 to 130 with an average of 98.1 which is included in the average category. A total of 14 students (50.00%) were in the average category, 4 students (14.29%) in the above average category, 3 students (10.71%) in the superior category, 4 students (14.29%) in the below average category, 3 students (10.71%) in the poor category, and 2 students (7.14%) in the very poor category. The research findings also showed that students' locomotor skills tended to be better than manipulatif skills. In general, students' basic motor skills have developed according to their age characteristics, but there are still gaps in abilities between students that require attention through a more structured and sustainable physical education learning program. The results of this study can be a basis for developing learning strategies oriented towards the development of basic motor skills of elementary school students.